Environmental Degradation and Food Security in Nigeria - Ogundipe, Adeyemi A.; Obi, Sophie; Ogundipe, Oluwatomisin M. (International Journal of Energy Economics and Policy, 2019)
This study investigates the effects of environmental degradation on food security in Nigeria using an annual data for the period 1970-2017. The theoretical framework was based on the Mathusian theory and the environmental Kuznets curve (EKC) hypothesis. The empirical model developed was estimated using the Johansen and vector error correction analysis. The empirical evidence suggest an inverse relationship between food production and environmental degradation implying that food security is threaten with rising degradation of the environment. In the same manner, food production responded inversely to gross domestic product per capita, hence justifying the EKC hypothesis. Since pollution is a rising function of income at the initial development stages, the rising pollution associated with income growth tends to hamper food security. On the other hand, the evidences reveal a positive influence of agriculture land and population growth on food production. However, the effect of the latter (population growth) is negligible suggesting that an increase in population results in lesser proportionate increase in food production, hence confirming the Mathusian theory. Keywords: Food Security, Environmental Degradation, Mathusian Theory, Environmental Kuznets Curve JEL Classifications: L66, Q15, Q56, Q53, H24 DOI: https://doi.org/10.32479/ijeep.8083